2001
DOI: 10.1046/j.1365-313x.2001.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

A tobacco nuclear extract supporting transcription, processing, splicing and modification of plant intron‐containing tRNA precursors

Abstract: SummaryNuclear tRNA genes are transcribed by RNA polymerase III (Pol III) and pre-tRNAs are processed into mature tRNAs via complex processes in the nucleus. We have developed an in vitro Pol III-dependent transcription system derived from tobacco cultured cells, which supports ef®ciently not only transcription of a variety of plant tRNA genes but also 5¢-and 3¢-end processing, nucleotide modi®cation and splicing of intron-containing pre-tRNAs. The structures of in vitro transcripts have been con®rmed by prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The yeast ligation pathway is known to require two components: tRNA ligase (Trl1p), to join the excised exons forming a splice junction 2Ј-phosphate , and the 2Ј-phosphotransferase Tpt1p to transfer the phosphate to NAD to form ADP-ribose 1Љ-2Љ-cyclic phosphate (Culver et al 1993;Spinelli et al 1997). Similar ligase activities have been found in plants and humans (Konarska et al 1982;Pick and Hurwitz 1986;Zillman et al 1991), and Tpt1p activity or functional orthologs have been found widely in plants, vertebrates, and archaea (Zillman et al 1992;Spinelli et al 1998;Yukawa et al 2001). However, the ligation pathway in some organisms may involve a completely different ligase, first discovered some time ago in vertebrates (Nishikura and De Robertis 1981;Filipowicz and Shatkin 1983;Laski et al 1983), that does not produce a 2Ј-phosphate junction.…”
Section: Splicing Conserved At the Outset But Not At The End?mentioning
confidence: 56%
“…The yeast ligation pathway is known to require two components: tRNA ligase (Trl1p), to join the excised exons forming a splice junction 2Ј-phosphate , and the 2Ј-phosphotransferase Tpt1p to transfer the phosphate to NAD to form ADP-ribose 1Љ-2Љ-cyclic phosphate (Culver et al 1993;Spinelli et al 1997). Similar ligase activities have been found in plants and humans (Konarska et al 1982;Pick and Hurwitz 1986;Zillman et al 1991), and Tpt1p activity or functional orthologs have been found widely in plants, vertebrates, and archaea (Zillman et al 1992;Spinelli et al 1998;Yukawa et al 2001). However, the ligation pathway in some organisms may involve a completely different ligase, first discovered some time ago in vertebrates (Nishikura and De Robertis 1981;Filipowicz and Shatkin 1983;Laski et al 1983), that does not produce a 2Ј-phosphate junction.…”
Section: Splicing Conserved At the Outset But Not At The End?mentioning
confidence: 56%
“…The quality of extracted RNA was tested on a 4% acrylamide/8 m urea gel. Primer extension analysis was carried out as described previously (Yukawa et al. , 2001) using 200 ng RNA and an FITC‐labelled primer (5′‐GGGACAACTCCAGTGAAAAGTTCTTCTC‐3′) complementary to the mGFP coding region.…”
Section: Methodsmentioning
confidence: 99%
“…A tobacco nuclear extract that supports transcription, processing, splicing and modification of tRNAs has been developed (Yukawa et al 1997;Yukawa et al 2000;Yukawa et al 2001) but separation and characterization of the biochemical activities has not been described, nor have similar systems been described in monocots.…”
Section: Discussionmentioning
confidence: 99%